Development of HoTS-Based Elementary Linear Algebra Course Test Instruments Charged With Islamic Character - Andi Ika Prasasti Abrar; Andi Kusumayanti (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2023)
This test is known as an evaluation tool or test instrument in the form of questions that are prepared in accordance with learning indicators. A lecturer should be able to provide questions that can trigger students to think at a higher level so that they can be more optimal in achieving learning objectives. This study aims to produce HOTS-based test instruments with Islamic characters by looking at the development procedures and quality of HOTS-based test instruments with Islamic characters developed. The type of development used is research research and development (RD), namely the development of test instruments for linear algebra courses. The development model used is a formative research (Tessmer) model which goes through 4 stages, namely preliminary, self-evaluation, prototyping (expert review, one to one, small group), and field test. The test subjects in this study were students of mathematics education class PMAT B, Faculty of Tarbiyah and Teacher Training, UIN Alauddin Makassar with a total of 33 students. Based on the results of the trials conducted, it was obtained that: (1) the test instrument was declared